Otherworld - Segel, Jason, 1980-; Miller, Kirsten, 1973- (Otherworld, 2017)
"After the newest set of virtual reality gear hits the market, Simon can't wait to test it out. But, when his friend Katherine suddenly disappears after being seen with men from the same gaming company, Simon must decide how far in the game he's willing to go to save her"--